2013
DOI: 10.1073/pnas.1300725110
|View full text |Cite
|
Sign up to set email alerts
|

Castor is required for Hedgehog-dependent cell-fate specification and follicle stem cell maintenance in Drosophila oogenesis

Abstract: Asymmetric division of stem cells results in both self-renewal and differentiation of daughters. Understanding the molecules and mechanisms that govern differentiation of specific cell types from adult tissue stem cells is a major challenge in developmental biology and regenerative medicine. Drosophila follicle stem cells (FSCs) represent an excellent model system to study adult stem cell behavior; however, the earliest stages of follicle cell differentiation remain largely mysterious. Here we identify Castor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 47 publications
13
89
2
Order By: Relevance
“…Recent studies provide evidence that these processes start at the border of the region between 2b and 3 of the germarium ( Fig. 1; Nystul and Spradling, 2010;Chang et al, 2013). Our data indicate, however, a strong upregulation of the two pathways already in region 2a and 2b (Fig.…”
Section: Discussion a Model Explaining The Formation Of Disorganised mentioning
confidence: 42%
See 1 more Smart Citation
“…Recent studies provide evidence that these processes start at the border of the region between 2b and 3 of the germarium ( Fig. 1; Nystul and Spradling, 2010;Chang et al, 2013). Our data indicate, however, a strong upregulation of the two pathways already in region 2a and 2b (Fig.…”
Section: Discussion a Model Explaining The Formation Of Disorganised mentioning
confidence: 42%
“…Individual egg chambers are connected by six to eight cells that form a 'stalk'. The specification of stalk cells starts in the germarium at the border between region 2b and 3 (Nystul and Spradling, 2010;Chang et al, 2013). This process involves at least two signalling events.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified two markers expressed in FSCs and their progeny: follicle cell nuclear antigens and Castor (Cas). Staining ovaries for either of these markers together with anti-FasIII reveals probable FSCs as positive for the marker but negative for FasIII (Chang et al, 2013;Hartman et al, 2013 3D), whereas in Pak mutant germaria, we saw additional, internal LanA accumulation, further evidence for internally positioned FSCs (Fig. 3E).…”
Section: Resultsmentioning
confidence: 88%
“…Adult ovaries were dissected, fixed and stained as previously described (Verheyen and Cooley, 1994). Primary antibodies used in this study were monoclonal anti-BicD [1B11, Developmental Studies Hybridoma Bank (DSHB); 1:10], mouse monoclonal anti-Hts 1B1 (DSHB; 1:5), mouse monoclonal antiHtsRC (DSHB; 1:20), mouse monoclonal anti-Fasciclin III (FasIII) (7G10, DSHB; 1:100), rabbit anti-GFP (G1544, Sigma; 1:500), rat monoclonal anti-Vasa (DSHB; 1:100), guinea pig anti-TJ (Li et al, 2003;1:5000), rabbit anti-β-galactosidase (ab616, Abcam; 1:2000), rabbit anti-Pak (Harden et al, 1996; 1:1000), rat monoclonal anti-DE-Cadherin (DCAD2, DSHB; 1:50), mouse monoclonal anti-Dlg (DLG1, DSHB; 1:5), mouse monoclonal anti-β-PS integrin (CF.6G11, DSHB; 1:2) and rabbit anti-Castor (Chang et al, 2013;1:500). Secondary antibodies were used at a 1:200 dilution and were conjugated to Cy5, FITC or TRITC.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Indeed, many epithelial stem cell lineages contain a transit-amplifying phase downstream from the stem cell division that is defined by incomplete differentiation. Both stem cells and transit-amplifying cells share similar morphology, remain mitotically active, and often express an overlapping set of molecular markers (Chang et al, 2013;Itzkovitz et al, 2011;Mascré et al, 2012;Yan et al, 2012). Moreover, epithelial stem cells are regularly lost from the niche and replaced by the daughter of a neighboring stem cell during normal homeostasis (Clayton et al, 2007;de Navascués et al, 2012;Margolis and Spradling, 1995;Snippert et al, 2010), indicating that transit-amplifying cells retain the capacity to re-enter the niche and assume the stem cell fate.…”
Section: Introductionmentioning
confidence: 99%